(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Induction of labour is a commonly used procedure for various gynaecological and obstetrical indications. Various pharmacological, mechanical and physical methods are used for it. Prostaglandins have been being used for it with variable results. However, Misoprostol has been now introduced reporting better results and lesser duration for induction of labour. Objective: To compare the mean time from induction to delivery with vaginal Misoprostol versus vaginal Prostaglandin E2 in females undergoing normal vaginal delivery at term. Material & Methods: This randomized control trial was conducted at Department of Obstetrics & Gynecology, Lady Aitchison Hospital, Lahore for 12 months from January, 2015 to December, 2015.A total of 100 patients were included in the study. They were randomly divided in two groups by using lottery method. In group A, patients received 25 microgram of the misoprostol vaginally and in group B, patients received 3 mg PGE2 vaginal tablet. At induction, time was noted. The misoprostol was repeated every 6 hours to a maximum of 5 doses. PGE2 was repeated after 6 hours to a maximum of 2 doses. All patients were followed-up till delivery of fetus and placenta. After delivery of placenta, time was noted again and total duration of induction to delivery was noted. All the data was entered and analyzed on SPSS version 20. Results: The mean age of the patients in the study was 28.61±6.57 years. Also the mean age, gestational age, parity and BMI were comparable in both groups. The mean duration of labour in group A was 7.42±1.74 hours and in group B was 9.80±2.59 hours (p-value=0.000). Also stratification for age, parity, BMI, gestational age and number of doses was done and was found significant in al of these factors. Conclusion: We conclude that vaginal misoprostol has significantly shorter duration of induction of labour as compared to PGE2 in females undergoing normal vaginal delivery at term. So we may use it routinely for induction of labour in our setup.